Konsep Metode Pembelajaran Ibn Khaldun dalam Pengajaran Bahasa Arab - Baiq Tuhfatul Unsi (Muróbbî: Jurnal Ilmu Pendidikan, 2018)
Ibn Khaldun's thoughts on Islamic education, especially the teaching of language as stated in the book of muqoddimah ibn khaldun, is still up to date until today. In his book Ibn muqoddimah ibn khaldun explains the malakah and tadrîj theories in which Ibn Khaldun targets the achievement of malakah and tadrîj. According to Ibn Khaldun, it is a discipline that develops expertise. Expertise can only be obtained by repetition of acts that make an impression in the brain so it becomes a habit. Ibn Khaldun said that the first thing that should be considered by an educator is the psychological condition of the child, and more importantly the educator must know the level of ability (intellect) and maturity of learners, Ibn Khaldun emphasized the application of educational methods should be gradually in accordance with the development of intellectual work with the reason that a child develops step by step and little by little in all aspects of the jasmaniyah and aqliyah as a whole. Thus, the concept of Ibn Khaldun’s method of learning is very relevant to be applied in the teaching of Arabic, because it is in harmony with theories of psychology and linguistics.